Estimating the area of extreme inclusions in Reissner–Mindlin plates. Issue 10 (3rd July 2022) - Morassi, Antonino; Rosset, Edi
Abstract : We derive upper and lower estimates of the area of unknown defects in the form of either cavities or rigid inclusions in Mindlin–Reissner elastic plates in terms of the difference δ W of the works exerted by boundary loads on the defected and on the reference plate. It turns out that the upper estimates depend linearly on δ W, whereas the lower ones depend quadratically on δ W . These results continue a line of research concerning size estimates of extreme inclusions in electric conductors, elastic bodies and plates.